P60 Pre-treatment IP-10 concentrations are associated with a sustained virological response in HIV/HCV co-infected patients. (6th September 2011) - Joshi, D; Bruce, M; Suddle, A; Taylor, C; Carey, I; Agarwal, K
Abstract : Introduction: Treatment of chronic HCV (cHCV) in HIV positive patients with pegylated interferon (PEG-IFN) and ribavirin (RIB) is associated with poorer treatment outcomes and an increased side effect profile. Strong immune T helper type 1 responses towards HCV determine outcome of infection. Interferon γ inducible protein 10 (IP-10) has been shown to correlate with treatment response in cHCV mono-infection but limited data are available for HIV co-infected patients. Aim: To investigate whether pre-treatment plasma levels of cytokines/chemokines differ between HIV/HCV co-infected and HCV mono-infected patients and whether they can predict response to PEG-IFN and RIB therapy. Method: Pre-treatment plasma samples were studied in HIV positive patients co-infected with cHCV and HIV negative cHCV patients. Plasma levels of IFN-γ, interleukin (IL)-2, IL-4, IL-6, IL-8, IL-10 and IP-10 (all pg/ml) were measured by ELISA. Patients were matched according to genotype, fibrosis stage and age. All patients were treated with PEG-IFN α 2a and weight based RIB for 24 weeks or 48 weeks according to genotype. All patients were previously treatment naive. Virological response was divided into SVR, non-response (NR) and responder relapse (RR). All results are presented as medians. Results: 37 HIV positive patients (CD4 count 495 cells/ml, undetectable HIV viral load in 86%) co-infected with HCV ([HCV viral load (VL) 1.68E6 IU/ml, 54% genotype 1, 7 (19%) patients with advanced fibrosis on biopsy (Ishak F>5)] were divided according virological response [n=23 SVR (62%), n=7 RR, n=7 NR]. 35 HIV negative patients with cHCV [HCV VL 2.12E6, 64% genotype 1, 5 (14%) patients with advanced fibrosis (Ishak F>5) were also divided according to virological response [n=23 SVR (66%), n=7 RR, n=6 NR]. Irrespective of HIV status, IP-10 (62 vs 105, p=0.006) and IL-6 (4 vs 7, p=0.03) levels were lower at baseline in patients who achieved an SVR. Baseline IP-10 (92 vs 49, p=0.009) and IL-8 (39 vs 22, p=0.01) were higher in the HIV positive group but the concentrations of IFN-γ, IL-2, IL-4, IL-6, IL-10 were similar between the two groups. In HIV positive patients baseline IP-10 concentrations were lower in those who achieved a SVR (84 vs 107 p=0.02) and also differed according to treatment response (SVR, 84 vs RR, 124 vs NR, 107 p=0.03). Conclusion: In our cohort IP-10 acted as a robust predictor of SVR among HIV/HCV co-infected and HCV mono-infected patients. IP-10 could serve as a pre-treatment biomarker to help identify patients who will achieve a SVR.